1-year quality of life and health-outcomes in patients hospitalised with COVID-19: a longitudinal cohort study - O’Brien, Kate; Townsend, Liam; Dowds, Joanne; Bannan, Ciarán; Nadarajan, Parthiban; Kent, Brian; Murphy, Niamh; Sheill, Gráinne; Martin-Loeches, Ignacio; Guinan, Emer (Respiratory research, 2022)
Published studies suggest physical recovery from the COVID-19 is complex, with many individuals experiencing persistent symptoms. There is a paucity of data investigating the longer-term trajectory of physical recovery from COVID-19. A prospective longitudinal design was utilised to investigate the impact COVID-19 has on physical functioning at 10-weeks (T1), 6-months (T2) and 1-year (T3) post-hospital discharge. Objective measures of recovery included 6-Minute Walk Test Distance (6MWTD), frailty (Clinical Frailty Scale), quantification of falls following hospital-discharge, return to work status and exercise levels. Subjective markers included symptoms (COVID-19-Specific Patient Concerns Assessment), fatigue (Chalder Fatigue Score) and health-related quality of life (HrQOL) [Short-Form-36 Health Survey Questionnaire (SF-36-II)]. Univariate analysis was performed using t-test, Wilcoxon rank-sum, and Chi-squared test, paired analysis using one-way analysis of variance and Krustal Wallis testing and correlation analysis with Spearman correlation tests. Sixty-one subjects participated. Assessments were conducted at a median of 55 days(T1), 242 days(T2), and 430 days(T3) following hospital-discharge. 6MWTD improved significantly overtime (F = 10.3, p < 0.001) from 365(209)m at T1 to 447(85)m at T3, however remained below population norms and with no associated improvement in perceived exertion. Approximately half (n = 27(51%)) had returned to pre-diagnosis exercise levels at T3. At least one concern/symptom was reported by 74%, 59% and 64% participants at T1, T2 and T3 respectively. Fatigue was the most frequently reported symptom at T1(40%) and T2(49%), while issues with memory/concentration was the most frequently reported at T3(49%). SF-36 scores did not change in any domain over the study period, and scores remained lower than population norms in the domains of physical functioning, energy/vitality, role limitations due to physical problems and general health. Return-to-work rates are low, with 55% of participants returning to work in some capacity, and 31% of participants don't feel back to full-health at 1-year following infection. Hospitalised COVID-19 survivors report persistent symptoms, particularly fatigue and breathlessness, low HrQOL scores, sub-optimal exercise levels and continued work absenteeism 1-year following infection, despite some objective recovery of physical functioning. Further research is warranted to explore rehabilitation goals and strategies to optimise patient outcomes during recovery from COVID-19. Hospitalised COVID-19 survivors report significant ongoing rehabilitation concerns 1-year following infection, despite objective recovery of physical functioning. Our findings suggest those who returned to exercise within 1-year may have less fatigue and breathlessness. The impact of exercise, and other rehabilitative strategies on physical functioning outcomes following COVID-19 should be investigated in future research.